The Effect of Medication Reminder Chart on Level Adherence in diabetes mellitus type 2 patients at RSUD Sleman Yogyakarta - Suffiana, Yunita; Rahmawati, Fita; Andayani, Tri Murti (INDONESIAN JOURNAL OF PHARMACY, 2017)
Patient adherence is a key factor that determines the outcome of diabetes mellitus therapy. This study was conducted to determine the effect of a medication reminder chart on level adherence and clinical outcome in patients with Type 2 diabetes mellitus. The experimental study used pretest-posttest design with control group was conducted during February until April of 2016 at Sleman Hospital in Yogyakarta. Patients were categorized into two groups of different subjects, who received of medication reminder chart tools were 40 patients (Code A) and the other 40 patients were assigned to control group (Code B). Morisky Medication Adherence Scale of 8-item (MMAS-8) was used to measure adherence. Clinical outcome were measured based on FBG decrease (mg/dl). Two independent sample t-test was using to determine the mean differences of the average score of the adherence level before and after using the medication reminder chart.Â  The results of this study showed that Medication Reminder Chart compared control groups improved adherence (p=0.000) but did not improve clinical outcome (p=0.411). The pharmacist might use The Medication Reminder Chart to improve medication adherence for chronic disease.